Representation of the Categories of Interdiscursivity and Intertextuality in a Scientific Text - Valiyeva Nargizakhon Zamir qizi; Dalieva Madina Khabibullaevna (International Journal on Integrated Education, 2021)
the article deals with the issues based on analyzing the categories of interdiscursivity and intertextuality in a scientific text. As it’s known that intertextual inclusions belong both to the sphere of linguistics and to the sphere of the knowledge that they transmit, we consider these linguistic phenomena as linguistic cognitive formations, characterizing which we can use both linguistic and cognitive parameters. In this article the author deals with the researches of scientists based on this topic and defines the categories of interdiscursivity and intertextuality and the role of allusion in the scientific text.